Spatiotemporal evolution characteristics and the driving force of habitat quality in the Qinghai–Tibet Plateau in topographic view (2000–2020) - Yu, Haotian; Qian, Xuexue; Jing, Haichao; Liu, Yinghui (Frontiers in Ecology and Evolution, 2024)
As a key indicator to evaluate biodiversity and eco-function, habitat quality shows the value of the ecosystem services. The Qinghai-Tibet Plateau occupies the highest elevation in the global dimension, where the regional environment is greatly affected by multiple factors including the terrain comprehensively. In the present study, InVEST model was employed to assess the habitat quality across varying terrain gradients. The study observed the displacement of the center of gravity of habitat quality under different topographical factors over the past 20 years to learn the trend of changes. Additionally, geo-detector model was enhanced to explore contribution rate of driving factors including biodiversity in different topographic position and overall. The results found that: (1) The habitat quality of Qinghai-Tibet Plateau was positively correlated with the terrain gradient, and the mean values of habitat quality increased with the gradual increase of terrain gradient. In the period between 2000 and 2020, mean habitat quality values within the study area exhibited a slight fluctuating trend with the spatial distribution characterized by higher values in the southeast and lower values in the northwest. (2) Among different terrain gradients, trends in the mean center's shift of habitat quality were diverse. The mean center of gradient Ⅰ went north but gradient V went west. The mean center of the habitat quality in gradient II-IV showed an uncertain trend. (3) The NDVI exerted the most vital influence on the quality of habitats irrespective of different terrain gradients. Annual mean temperature, soil type and slope occupied 2-4 places in each terrain. The study indicates that in the last two decades, the habitat quality on the Qinghai-Tibet Plateau has gradually increased across different terrain locations. In terms of policies to protect habitats, terrain should be classified and targeted accordingly.